Cultural Integration on Geometry Lesson: The Impact of Traditional Game-Based Learning on Students' Creative Thinking - Lestari, Dina Puji; Anwar, Lathiful; Sa’dijah, Cholis; Abdul Rahim, Suzieleez Syrene; Hafiizh, Mochammad (Journal of Ecohumanism, 2024)
This study investigates the impact of traditional game-based teaching on the geometry students' creativity, emphasizing similarity and parallelism concepts. Creative thinking is important in education, but memorization typically overshadows it. Traditional games can connect the curriculum to students' cultures and boost engagement and creativity. A quasi-experimental design with a pre-test and post-test control group of 40 students assigned 24 to the experimental group, which received traditional games training, and 16 to the control group, which received conventional instruction. Students' fluency, flexibility, and originality were tested, and N Gain scores rated their improvement. The findings showed that the students in the experimental group excelled further than the students in the control group on all of the measures of creative thinking. The results achieved the most significant enhancement in fluency and flexibility while there was a less significant increase in originality. This indicates that playing traditional games helps students to come with ideas and diversify their approaches but would necessitate other activities to develop originality. The intervention also exhibited the effectiveness of culturally relevant pedagogy in combining the students’ cultural background and sociometric ideas by making geometry more appealing. To deepen the understanding of how traditional games affect students’ creative thinking further research should have a larger population, extended duration of the intervention and more games to ensure better understanding of the long-term effects and originality improvements. The originality of this study is centered on the fact that cultural assets can be embedded into classroom activities and shows the importance of using traditional games such as Gobak Sodor in promoting students’ creative and mathematical thinking as well as their cultural identity in a holistic way.